PID-Based Load Frequency Control for Smart Grid Applications - Osundina, Emmanuel Mayowa; Sonola, Moyosoluwalorun Odunayo; Osungbohun, Olumide Cornelius; Oritsetimeyin, Tim Peter; Peter Daffin Onwe; Eluebo Emmanuel Chuka; Oluwole , Olumide Ifedapo; Odama, Gregory Okwor; Sazgar Abdualaziz Wali; Yifan Hu; Duberney Florez (Frontier Advances in Applied Science and Engineering, 2024)
Ensuring stable frequency and power balance in modern power systems is essential, particularly within smart grids and advanced multi-area configurations. This study evaluates an enhanced control strategy employing Proportional-Integral-Derivative (PID) controllers for load frequency control in a three-area grid system, which represents scenarios found in power networks with dynamic loads and inter-area power transfers. Using MATLAB/Simulink, a three-area model was developed to simulate the application of PID controllers within the secondary control loop of Automatic Generation Control (AGC). The simulation results indicated significant improvements in frequency regulation and tie-line power variations, demonstrating the efficacy of PID controllers in bolstering stability and performance in complex, interconnected systems.